KAJIAN PERUBAHAN LAHAN MENJADI PERMUKIMAN DAN KARAKTERISTIKNYA DI DAERAH ALIRAN SUNGAI (DAS) CILIWUNG BAGIAN HILIR - Aslinda, Nindy; Syartinilia, . (Jurnal Lanskap Indonesia, 2016)
Ciliwung Watershed is one of watershed that across the Jakarta capital region. Ciliwung Watershed is categorized as super-priority watershed in Indonesia. The study was conducted in downstream of Ciliwung Watershed in Jakarta. This study aimed to analyze land cover changes from greenery open space to build up area in period of 1993-2013 and to analyze the distribution of settlement and its characteristics in the downstream of Ciliwung Watershed. LANDSAT images data of 1993 and 2013 were classified using supervised classification method to produce land cover map. The results of the map are analyzed spatially and descriptively to determine the changes. The greenery open space have changed into built up area about 70.07% during 20 years in the downstream of Ciliwung watershed. While, the settlement is dominated by the unplanned settlement (87.23%). Meanwhile, the settlements were dominated by unplanned settlements (87.23%) which characterized by linier settlement patterns, very lage size of settlement, low to medium building density, and good condition of insfrastructure. Five recommendations have provided for landscape managing of settlement in downstream of Ciliwung Watershed.